Being a Spinozist today: Some considerations on eternity, happiness and philosophy - Sole, Maria Jimena (2020)
This paper is a response to Andrea Sangiacomo’s invitation to participate in an exchange on the currency of Spinoza’s philosophical project and to discuss whether Spinoza’s overall project is worth pursuing as philosophy. Sangiacomo’s provocative paper titled “Spinoza’s mistake: the desire for eternal joy” –intended to trigger the discussion– argues that Spinoza’s conception of happiness as amor Dei intellectualis, an infinite and eternal joy, rests upon a conceptual error, namely, that no affect (including this intellectual love of God) can be eternal. I believe his criticism entails a conception of eternity not shared by Spinoza himself. Thus, I argue that eternity and duration, although they are different spheres, are not opposing ones and I show that Spinoza understands eternity and duration as two perspectives from which we can conceive of the existence of things. Furthermore, it is my opinion that Spinoza’s conception of happiness is intimately connected with the understanding of adequate knowledge as action and makes it possible to vindicate Spinozism as a valuable and current philosophy. The second section of this writing briefly develops this viewpoint, concentrating on the value of Spinoza’s conception of philosophy as a transformative praxis.